2020
DOI: 10.2147/cmar.s245696
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oxymatrine Inhibits Proliferation and Migration of Vulvar Squamous Cell Carcinoma Cells via Attenuation of the RAS/RAF/MEK/ERK Pathway</p>

Abstract: Purpose: To evaluate the anti-tumor effects of oxymatrine in vulvar squamous cell carcinoma (VSCC) cells and to explore the underlying mechanisms. Methods: We selected SW962 and A431 VSCC cell lines. Cell proliferation was examined using MTT assay. Cell cycle and apoptosis were detected using flow cytometry. Migration and invasion were evaluated using transwell and wound-healing assays. The relevant protein expression and signaling pathways were analyzed using Western blotting. Results: Oxymatrine inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Oxymatrine can induce pancreatic cancer cells apoptosis through affecting the ratio of Bax/ Bcl2 and release of mitochondrial cytochrome c, 18 and cause the human bladder cancer cell apoptosis and cell cycle arrest. 19 Oxymatrine inhibits cell proliferation via attenuation of the RAS/ERK pathway, 20 abolishing the PI3K expression, 21,22 suppression of EGFR signaling, 15 and deactivating STAT5. 23 Furthermore, oxymatrine combined with chemotherapeutic agents could enhance their anti-cancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…Oxymatrine can induce pancreatic cancer cells apoptosis through affecting the ratio of Bax/ Bcl2 and release of mitochondrial cytochrome c, 18 and cause the human bladder cancer cell apoptosis and cell cycle arrest. 19 Oxymatrine inhibits cell proliferation via attenuation of the RAS/ERK pathway, 20 abolishing the PI3K expression, 21,22 suppression of EGFR signaling, 15 and deactivating STAT5. 23 Furthermore, oxymatrine combined with chemotherapeutic agents could enhance their anti-cancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…By detecting cell apoptosis, it was found that oxymatrine can enhance the expression of cleaved asparaginase 3 and Bax, and attenuate the expression of Bcl-2, which further leads to the increase of apoptosis, indicating that oxymatrine can increase the vulvar scale. Antitumor effect of vulva squamous cell carcinoma(VSCC)cells ( 34 ). Similarly, matrine not only reduces the expression level of Bcl-2 and increases the expression of caspase-8, but also inhibits the viability, and migration and induces apoptosis of ovarian cancer cells by up-regulating the p38MAPK and JNK pathways ( 35 ).…”
Section: Apoptosis and Immunogenic Cell Deathmentioning
confidence: 99%
“…The ERK/MAPK pathway regulates a variety of cellular activities, including cell growth and signal transduction (38). A large number of studies have shown that the ERK/MAPK pathway in cancer can regulate the expression of c-Myc mRNA and promote the stability of c-Myc, thus promoting the growth of cancer cells (39)(40)(41)(42). In addition, the ERK/MAPK signaling can increase tumor invasion and metastasis by upregulating the expression of MMP2 and MMP9 (43)(44)(45).…”
Section: Expression Of Ppp1r14dmentioning
confidence: 99%
“…Therefore, it can be observed that PPP1R14D knockdown did reduce the expression of BRAF/MEK/ERK signaling pathway proteins. Since several previous studies (39)(40)(41)(42)(43)(44)(45) have shown that the ERK/MAPK signaling pathway acts as upstream proteins to regulate c-MYc, MMP2 and MMP9 proteins, it was hypothesized that the reduced expression of c-Myc, MMP2 and MMP9 proteins was regulated by ERK/MAPK signaling pathway after PPP1R14D knockdown. However, the internal mechanism of the ERK/MAPK signaling pathway in regulating c-Myc, MMP2 and MMP9 proteins after PPP1R14D knockdown was not thoroughly explored, which is a further limitation to the current study.…”
Section: Expression Of Ppp1r14dmentioning
confidence: 99%